Analysis of internal and external dimensions of social performance from the perspective of managers: The case of Zoomarine Algarve - Contreiras, J.; Machado, V.; Duarte, A.P. (I International Congress - Interdisciplinarity in Social and Human Sciences, 2016)
The study here presented is part of a larger research project on sustainable tourism and corporate social responsibility (CSR) based on the case study of the theme park Zoomarine Algarve. The study aimed to understand the vision of managers on the company’s social performance, by identifying the strategy and the main socially responsible practices implemented. As part of this qualitative study, five semi-structured interviews were conducted to the CEO and the managers of departments. The information gathered from the interviews allowed the completion of a social responsibility scorecard that characterizes and assesses the company's performance in seven dimensions: ethical and socially responsible culture, environment, customers, suppliers, employees, shareholders and community. The score obtained in the various dimensions in evaluation was positive, particularly with regard to the relationship with customers, suppliers, employees and the community.